A Glimpse Into the Mental Health of Graduate Students in Health Science Professions at One Educational Institution...American Occupational Therapy Association (AOTA) INSPIRE Annual Conference & Expo, April 20-23, 2023, Kansas City, Missouri - Muskatallo, Erin; Coppola, Andrea; Fisher, Sara; SanGiacomo, Amber; Reading, Emma Kathleen (American Journal of Occupational Therapy)
Date Presented 04/22/2023 This poster highlights results from a cross-sectional research study that examined stress, anxiety, and depression levels; sources of stress; and coping mechanisms of graduate students in health science programs at one educational institution. Primary Author and Speaker: Erin Muskatallo Additional Authors and Speakers: Sara Fisher, Amber SanGiacomo, Emma Kathleen Reading Contributing Authors: Andrea Coppola